PELATIHAN PENYUSUNAN MODUL AJAR BERDIFERENSIASI DAN MODUL P5 DI SMP NEGERI 1 BUAY MADANG OKU TIMUR - Arini Rosa Sinensis; Marlina Marlina (Jurnal Abdi Insani, 2026)
The implementation of the Merdeka Curriculum requires teachers to develop innovative teaching modules, including differentiated instruction and the integration of the Pancasila Student Profile Strengthening Project (P5). However, the initial understanding of teachers at SMP Negeri 1 Buay Madang, East OKU, regarding these aspects was relatively low, at approximately 25%. This community service activity aimed to enhance teachers’ competencies in designing differentiated teaching modules and integrating P5. The implementation methods included providing motivation, delivering instructional materials, conducting hands-on training in module development guided by expert facilitators, as well as organizing question-and-answer sessions and discussions. A total of 40 teachers actively participated in this activity. Data were collected using questionnaires and analyzed with a Likert scale approach. The results demonstrated a significant improvement in teachers’ understanding, increasing from 25% to 70% after the mentoring program. This indicates that the applied methods were effective in enhancing teachers’ professional capacity. The activity contributed positively to supporting the implementation of the Merdeka Curriculum and promoting more relevant, student-centered learning. Continuous training is recommended to ensure the sustainability of these positive outcomes.